2019
DOI: 10.1152/ajprenal.00356.2018
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic interval exercise improves renal functionality and affects mineral metabolism in obese Zucker rats

Abstract: Obesity, metabolic syndrome, and renal injury are considered risk factors for type 2 diabetes, as well as kidney disease. Functional and structural changes in the kidney as consequence of obesity and metabolic syndrome may lead to impaired mineral metabolism in what is known as chronic kidney disease-mineral and bone disorder. Lifestyle interventions such as physical activity are good strategies to manage these pathologies and therefore, prevent the loss of kidney functionality and related complications in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Exercise is one of the effective rehabilitation methods to delay aging, which may delay the aging of skeletal muscle and brain tissue (28-30). Previous studies have indicated that exercise may also improve glomerular filtration function and glomerulosclerosis in obese individuals (31). Furthermore, the effect of exercise on improving renal fibrosis caused by disease in models has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is one of the effective rehabilitation methods to delay aging, which may delay the aging of skeletal muscle and brain tissue (28-30). Previous studies have indicated that exercise may also improve glomerular filtration function and glomerulosclerosis in obese individuals (31). Furthermore, the effect of exercise on improving renal fibrosis caused by disease in models has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention period was followed by an additional 6-week weight-maintenance period of dietary treatment with a standard rat chow diet (WM21) combined or not with the training protocol (e or s, respectively) and the pharmacological treatment (AM) to maintain the weight lost during the previous intervention period of three weeks. A) average daily caloric intake (kcal/day) along the different experimental stages (DIO, weight-loss intervention, and weight-maintenance), B) average body weight at the end of the different experimental stages, C) bodyweight/ femur length ratio (g/cm 2 Throughout the experimental period, and due to the higher caloric content of HFD, a significantly higher caloric intake was exhibited by HFD-treated rats when compared to their normocaloric controls. Likewise, higher body weight was gained by the former animals.…”
Section: Combined Weight Control Strategies Efficiently Achieve Weighmentioning
confidence: 99%
“…They lead to adverse metabolic effects on blood pressure, cholesterol, triglycerides, and insulin resistance. This compilation of factors is known as metabolic syndrome (MetS) 1 , which is directly related to cardiovascular disease and the alteration in other vital functions, such as the renal function 2 . MetS prevalence is estimated to be between 10 and 30%, increasing sharply in older age-groups in most European countries 3 and it is likely that it will continue to rise in the future given the persistently rising trends in obesity, especially among young people.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the literature show that moderate physical activity can reduce inflammation and improve general physical function in humans [1][2][3][4][5][6][7][8][9] and animals [10,11]. In a rat model, aerobic interval exercise protocol was shown to prevent the development of diabetic nephropathy and to affect the metabolism of certain minerals [12]. Moreover, aerobic training in association with L-arginine supplementation also demonstrated to ameliorate kidney and liver damage in myocardial infarction rats, via antioxidant mechanisms [13].…”
Section: Introductionmentioning
confidence: 99%